Live Video Analysis Platform for Continuous Driver State Evaluation and Proactive Accident Prevention Through Face Detection Technology - Raman R A, Dr.B.Latha (Cuestiones de Fisioterapia, 2025)
The transportation sector is continuously evolving with the integration of advanced safety mechanisms aimed at reducingaccidents and safeguarding lives. This project introduces an innovative safety system specifically designed for electric buses,utilising Continuous Rapid Eye Motion Detection (CREM) technology. The system is bifurcated into two primary modules:software and hardware. The software module leverages Python programming and face detection algorithms to monitor thedriver's eye status in real-time.